EPIDEMIOLOGY AND HEALTH IN TRANSIT: THE SUBJECTIVITY REVEALED BY TRUCK DRIVERS THROUGH THEIR RISK BEHAVIORS IN TRAFFIC - Galgani da Fonseca, Gema; Tatiane Pimenta, Jéssika; Antônio da Silva, Nilson (Health and Society, 2024)
Traffic is a social phenomenon in which it portrays the structural disposition and positioning of man - machine, in reciprocal interaction and movement with the influences of the social environment, when the dimension of subjectivity breaks with the dichotomies ensnared in modern thought, such as; individual/society, intellectual/emotional, internal/external through a theoretical model on the human psyche from its generative character within the cultural fabric in which people and groups participate. The subject of this study is justified by the fact that, in this social context in which human subjectivities - truck drivers and their risky behaviour - converge, traffic is characterized as an environmental and interdisciplinary phenomenon. To this end, bibliographic sources were searched on various interfaces related to the man-machine dyad, using data sources such as Google Scholar, the Virtual Health Library (VHL), scientific articles and statistical data source platforms. The results related to risk behaviors encompassed the human fact as one of the most impactful (adding other adversities such as fear of dismissal, symptoms of stress, anxiety, competitiveness, homesickness, burnout, psychological and psychiatric illness, victims of violence and traffic accidents, substance abuse); the use of the driver-machine relationship «the house is your truck» and the influences on the issue of driver and passenger vulnerability is a factor that causes numerous accidents. Therefore, in the face of contemporary demands involving pressure and a race against time, a high level of responsibility related to loads and transportation, stressful situations and a lack of healthier psycho-emotional resources is a watershed, determining the life or death of many individuals moving between their worlds. Further research correlating the dimension of human subjectivity is therefore fruitfully suggested, with a view to aligning the profession of truck drivers with safer traffic, promoting the reframing of this phenomenon and safer traffic and preservation of life.